Too smart for their own good: Trading truthfulness for efficiency in the Israeli medical internship market - Ariel Rosenfeld; Avinatan Hassidim (Judgment and Decision Making, 2020)
The two most fundamental notions in mechanism design are truthfulness and efficiency. In many market settings, such as the classic one-sided matching/assignment setting, these two properties partially conflict, creating a trade-off which is rarely examined in the real-world. In this article, we investigate this trade-off through the high-stakes Israeli medical internship market. This market used to employ a standard truthful yet sub-optimal mechanism and it has recently transitioned to an ``almost'' truthful, more efficient mechanism. Through this in-the-field study, spanning over two years, we study the interns' behavior using both official data and targeted surveys. We first identify that substantial strategic behaviors are exercised by the participants, virtually eliminating any efficiency gains from the transition. In order to mitigate the above, we performed an intervention in which conclusive evidence was provided showing that, for most of the interns, reporting truthfully was much better than what they actually did. Unfortunately, a re-examination of the market reveals that our intervention had only minor effects. These results combine to question the practical benefits of ``almost'' truthfulness in real-world market settings and shed new light on the typical truthfulness-efficiency trade-off.